Circular dichroism in laser-assisted proton-hydrogen collisions - Niederhausen, Thomas; Feuerstein, Bernold; Thumm, Uwe (My University, 2004)
We investigate the effects of a strong laser field on the dynamics of electron capture and emission in ion-atom collisions within a reduced dimensionality model of the scattering system in which the motion of the active electron and the laser electric field vector are confined to the scattering plane. We examine the probabilities for electron capture and ionization as a function of the laser intensity, the projectile impact parameter b, and the laser phase ϕ that determines the orientation of the laser electric field with respect to the internuclear axis at the time of closest approach between target and projectile. Our results for the b-dependent ionization and capture probabilities show a strong dependence on both ϕ and the helicity of the circularly polarized laser light. For intensities above 5×1012W/cm2 our model predicts a noticeable circular dichroism in the capture probability for slow proton-hydrogen collisions, which persists after averaging over ϕ. Capture and electron emission probabilities defer significantly from results for laser-unassisted collisions. Furthermore, we find evidence for a charge-resonance-enhanced ionization mechanism that may enable the measurement of the absolute laser phase ϕ.